Relationship between serum soluble suppression of tumorigenicity (ST) 2 and global longitudinal strain in early onset preeclampsia - Hawani Sasmaya Prameswari; Cut Azlina Effendi; Achmad Fitrah Khalid; Setyorini Irianti; Ita Fatati; Mohammad Rizki Akbar (BMC Cardiovascular Disorders, 2024)
Abstract Background Preeclampsia is one of the leading causes of death in childbearing women worldwide. Hemodynamic changes in preeclampsia can trigger cardiac remodeling as indicated by increase of soluble-ST2 (sST2). Global longitudinal strain were able to detect systolic dysfunction better than the ejection fraction. This study aims to evaluate the correlation between serum levels of sST2 towards GLS in patients with early-onset preeclampsia. Methods This is a cross-sectional observational study with correlation analysis. Subjects were patients with severe preeclampsia with gestational age before 34 weeks at Dr. Hasan Sadikin Central General Hospital Bandung and Bandung Kiwari Regional General Hospital from June to August 2022. Examination of sST2 was carried out through blood samples using the ELISA method. sST2 was measured using Presage ST2 Assay reagent. GLS examination was carried out using speckle tracking technique with EchoPAC. Correlation analysis was conducted using the Pearson test if normally distributed, otherwise Spearman’s correlation was conducted. Correlation analysis was followed by linear regression. Results A total of 30 patients met the inclusion criteria. The mean age was 30.83 ± 7.09, with 17 (56.7%) multiparous patients. The median sST2 was 145.75 ng/mL, and the median GLS was − 17.4%. Spearman correlation analysis showed that there was a significant positive correlation with moderate strength between sST2 and GLS (r = 0.583; p < 0.002). Linear regression showed that every 1 ng/ml increase in sST2 would give an increase in GLS of 0.014%. Conclusion There is a significant correlation between sST2 and GLS in patients with early onset severe preeclampsia.